Greenwood regeneration status in community forests of Chiti Lamjung Nepal (Geographical Journal of Nepal, 2023)
Forest regeneration is the process by which new tree seedlings become entrenched after forest trees have been harvested or destroyed by fire, insects, or diseases. The process is key to sustainable forestry and can be accomplished through natural regeneration, which occurs when new seedlings or sprouts are produced by trees left on or near the site. The study is to calculate the regeneration status of the tree species in community-managed forests. The sampling points were generated by using the random table. The sample quadrate size was taken 20m×20m for a tree, 5m×5m for a sapling, and 1m×1m for the seedling. In five community forests, altogether 30 quadrates were taken for a tree, 60 nested quadrates were taken for a sapling and 120 nested quadrates were taken for a seedling. The tree layer, sapling layer and seedling layer were differentiated by taking reference tothe Diameter at Breast Height (DBH) class. An individual having DBH ≥ 5cm is considered a tree, an individual having DBH value between 1cm to < 5cm is considered a sapling, and individuals having 1cm to < 5cm DBH are considered as a seedling. The DBH distribution curve was obtained by plotting diameter class in x- axis and density on y- axis. All studied community forests are mixed forest dominated by tree species Castanopsis indica, Diospyros embryopteris (Diospyros malabarica), Shorea robusta, and Schima wallichii (Schima wallichii choisy). The regeneration potential of the Tilahar community forest(CF) is found high despite high grazing and other human intervention. The DBH class distribution curve of tree species is found as inverse J-shape, indicating that the overall forest has a sustainable regeneration.